Analisis Keterampilan Riset Sains dan Pemahaman Konsep Mahasiswa Eksperimen Gelombang Mekanik Laboratorium Nyata dan Virtual Diferensiasi: Analysis of Science Research Skills and Students' Conceptual Understanding of Real and Virtual Laboratory Mechanical Wave Experiments Differentiation - Hifni Aulia Adifina; Ani Rusilowati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The low quality of education in Indonesia is partly due to inadequate teaching resources. One way to improve the quality of teaching resources is to apply 21st-century skills through research activities and to develop conceptual understanding. This study aims to analyze students' scientific research skills and conceptual understanding of mechanical wave phenomena through a differentiation approach using a real and a virtual laboratory. The method used in this study is a quasi-experimental design. The study's population consisted of students in the Physics Education study program at Semarang State University. The sample for this study consisted of students in the Physics Education study program at Semarang State University, with class A as the control class and class B as the experimental class, determined using a purposive sampling technique. The control class conducted experimental activities using a differentiation approach in a real laboratory, while the experimental class conducted them in a virtual laboratory. The instruments used were both test and non-test (observations and documents). The analysis techniques used in this study included descriptive statistics and inferential statistics. The results showed that the scientific research skills of students in the control class met the good criteria (78.3%), while those in the experimental class met the very good criteria (83%). The results of students' conceptual understanding in the control and experimental classes met the good criteria, with percentages of 75.6% and 79.6%, respectively. This study concluded that there was a significant difference in science research skills between students who conducted experiments in real laboratories and those who conducted experiments in virtual laboratories. Still, there was no significant difference in conceptual understanding between the two groups.